Streets of Laredo - Larry Mcmurtry (UK Orion Books, 1994)
Pits legendary Texas Ranger Woodrow Call against his deadliest adversary ever.
Keywords: Literature (3GdCOHs; General -- Fiction; Outlaws; A Novel